2022
DOI: 10.1186/s12935-022-02494-1
|View full text |Cite
|
Sign up to set email alerts
|

FERMT1 contributes to the migration and invasion of nasopharyngeal carcinoma through epithelial–mesenchymal transition and cell cycle arrest

Abstract: Background Fermitin family member 1 (FERMT1) is significantly overexpressed in human cancers and associated with poor prognosis, but its contributions to tumorigenesis and nasopharyngeal carcinoma (NPC) progression remain unclear. Methods The public GEO database was examined to investigate the role of FERMT1. Immunohistochemistry (IHC) staining of FERMT1 was performed in NPC tissues to corroborate the results. Western blotting and qRT-PCR were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…FERMT1 is essential to maintain cell-matrix adhesion as an integrin-interacting protein. The overexpression of FERMT1 was found in multiple tumors such as colon cancer, gastric cancer, oral squamous cell carcinoma, and nasopharyngeal carcinoma, and has been associated with metastasis and poor prognosis [ 9 , 10 , 11 , 12 ]. FERMT1 was highly expressed in epithelial non-small-cell lung cancer (NSCLC), but not in neuroendocrine NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FERMT1 is essential to maintain cell-matrix adhesion as an integrin-interacting protein. The overexpression of FERMT1 was found in multiple tumors such as colon cancer, gastric cancer, oral squamous cell carcinoma, and nasopharyngeal carcinoma, and has been associated with metastasis and poor prognosis [ 9 , 10 , 11 , 12 ]. FERMT1 was highly expressed in epithelial non-small-cell lung cancer (NSCLC), but not in neuroendocrine NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of Kindlins, fermitin family member 1 (FERMT1, also known as Kindlin-1) is related to Kindler syndrome (KS), a genetic disorder that mainly affects the skin and intestine [ 8 ]. Moreover, abnormal FERMT1 expression has been described in several cancers, including colon cancer [ 9 ], gastric cancer [ 10 ], oral squamous cell carcinoma [ 11 ] and nasopharyngeal carcinoma [ 12 ]. FERMT1 is considered to be involved in tumor proliferation, apoptosis, metastasis, and tumor angiogenesis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…DEGs analysis was performed using the DESeq. 2 software, and pairwise comparisons were analyzed using edgeR 15 . Genes meeting the criteria of a false discovery rate (FDR) ≤ 0.05 and a fold change ≥2 were identified as DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…2 software, and pairwise comparisons were analyzed using edgeR. 15 Genes meeting the criteria of a false discovery rate (FDR) ≤ 0.05 and a fold change ≥2 were identified as DEGs. The clusterProfiler package was utilized to conduct functional enrichment analysis of module genes in specific Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways.…”
Section: Differential Expressed Genes (Degs) Analysismentioning
confidence: 99%
“…Kindlin-1 is primarily located in the epidermis, although it is also expressed in the colon, stomach, and kidneys to a lesser extent 11 . A previous study found that FERMT1 is a central tumor driver in cutaneous epithelial cells 12 . Loss-of-function mutations of FERMT1 cause a rare and recessive genodermatosis known as Kindler syndrome, which increases the risk of developing squamous cell carcinomas 13 .…”
Section: Introductionmentioning
confidence: 94%